Assessment of liver function tests in pregnant women at a tertiary care center - Kaur, Kanwaljeet (International Journal of Psychosocial Rehabilitation, 2008)
Assessment of liver function tests in pregnant women at a tertiary care centerDr. Kanwaljeet KaurAssistant Professor, Department of Pathology, Sri Guru Ram Das Institute of Medical Sciences & Research, Amritsar, PunjabABSTRACTBackground: Liver physiology may change during pregnancy, which later on may progress to liver disease. The severity of the disease is related to morbidity and mortality. The present study was conducted to assess liver function tests (LFT) in pregnant women at a tertiary care center.Materials & Methods: 74 pregnant women with abnormal LFT were carefully examined. Symptoms were recorded. The definition of abnormal LFT pertained to values higher than the normal range as defined by the local laboratory (bilirubin >24mol/L, alkaline phosphatase (ALP) >103 U/L, gamma-glutamyltranspeptidase (GGT)>26 U/L, ALT >51 U/L, aspartate aminotransferase (AST)>33 U/L).    Results: In 1st trimester causes of abnormal LFT was hyperemesis gravidarum in 36, typhoid in 4. In 2nd trimester, hyperemesis gravidarum in 5 and choledocholisthesis in 3. In 3rd trimester, acute fatty liver of pregnancy in 6, drug induced in 4, HELLP syndrome in 1, hepatitis B flare in 3, intrahepatic cholestasis of pregnancy in 3, PET in 2, partial HELLP syndrome in 3 and unknown in 4 cases. The difference was significant (P< 0.05). LFT in Hyperemesis Gravidarum, PET and partial HELLP Syndrome such as total bilirubin (µmol/L) was 22.5, 14.6 and 15.4, in ALP (U/L) was 53.5, 201.5 and 192.1, in GGT (U/L) was 43.8, 17.3 and 35.8, in ALT (U/L) was 101.5, 112.8 and 143.6, in AST (U/L) was 74.2, 64.2 and 83.7 and albumin (g/L) was 35.3, 29.5 and 32.5 respectively. The difference was significant (P< 0.05).Conclusion: Anxiety can be reduced and proper obstetric planning for the delivery date can be made possible by being aware of the probable causes of an abnormal LFT at different stages of pregnancy.  Given the possibility of a more severe seroconversion reaction in the immediate postpartum period, more care should be used when evaluating an obstetric patient's abnormal LFT if they have HBsAg.